Effect on adhesion of a nanocapsules-loaded adhesive system - Bruna Genari; Vicente Castelo Branco Leitune; Denise Soledade Jornada; Bibiana Rocha Aldrigui; Adriana Raffin Pohlmann; Sílvia Stanisçuaski Guterres; Susana Maria Werner Samuel; Fabrício Mezzomo Collares (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This study aimed to evaluate the in situ degree of conversion, contact angle, and immediate and long-term bond strengths of a commercial primer and an experimental adhesive containing indomethacin- and triclosan-loaded nanocapsules (NCs). The indomethacin- and triclosan-loaded NCs, which promote anti-inflammatory and antibacterial effects through controlled release, were incorporated into the primer at a concentration of 2% and in the adhesive at concentrations of 1, 2, 5, and 10%. The in situ degree of conversion (DC, n=3) was evaluated by micro-Raman spectroscopy. The contact angle of the primer and adhesive on the dentin surface (n = 3) was determined by an optical tensiometer. For the microtensile bond strength µTBS test (12 teeth per group), stick-shaped specimens were tested under tensile stress immediately after preparation and after storage in water for 1 year. The data were analyzed using two-way ANOVA, three-way ANOVA and Tukey's post hoc tests with α=0.05. The use of the NC-loaded adhesive resulted in a higher in situ degree of conversion. The DC values varied from 75.07 ± 8.83% to 96.18 ± 0.87%. The use of NCs in only the adhesive up to a concentration of 5% had no influence on the bond strength. The contact angle of the primer remained the same with and without NCs. The use of both the primer and adhesive with NCs (for all concentrations) resulted in a higher contact angle of the adhesive. The longitudinal μTBS was inversely proportional to the concentration of NCs in the adhesive system, exhibiting decreasing values for the groups with primer containing NCs and adhesives with increasing concentrations of NCs. Adhesives containing up to 5% of nanocapsules and primer with no NCs maintained the in situ degree of conversion, contact angle, and immediate and long-term bond strengths. Therefore, the NC-loaded adhesive can be an alternative method for combining the bond performance and therapeutic effects. The use of an adhesive with up to 5% nanocapsules containing indomethacin and triclosan and a primer with no nanocapsules maintained the long-term bond performance.